Angiolymphoid Hyperplasia With Eosinophilia: New Concept to Lower Recurrence. Issue 5 (July 2019) - Labib, Amir; Estawrow, Mina
Abstract : Abstract: Angiolymphoid Hyperplasia with Eosinophilia (AHLE) is a rare benign vascular disorder of unknown etiology. While World Health Organization recognizes it as a benign neoplasm, its progressive nature and high recurrence rate are consistent with being a locally malignant tumor. It may present as solitary or multiple nodules with more predilection to head and neck region, especially auricular area. Despite variety of available treatment options, high recurrence rate remains a compelling issue. The spectrum of these treatment modalities includes topical or systemic steroids use, intralesional injection of certain materials such as Bleomycin, Vinblastine or interferon, or even surgical excision. In our study, the authors present a case of middle-aged female with recurrent AHLE in left concha and preauricular region. Excision of the lesion with 4 mm of the normal surrounding skin, preserving auricular cartilage, was done while the resultant defect was covered by grafted Temporoparietal Fascia Flap. Our 1-year follow-up period showed aesthetically accepted outcome with no recurrence. The authors hypothesize that treating AHLE as a locally malignant tumor by excising the lesion with 4 mm safety margin decreases recurrence rates. Moreover, reconstruction by grafted temporoparietal fascia flap achieves a reasonable aesthetic outcome with minimal donor site morbidity.